Overlapping Multiple Assignments - Jörgen Kratz (Lund University, School of Economics and Management, Department of Economics, 2014)
This paper studies an allocation problem with multiple assignments, indivisible objects, no endowments and no monetary transfers, where a single object may be assigned to several agents as long as the set of agents assigned the object satisfy a compatibility constraint. It is shown that, on the domain of complete, transitive and strict preferences, group-sorting sequential dictatorships are fully characterized by four different combinations of coalitional strategyproofness, strategyproofness, Pareto efficiency, non-bossiness, group-monotonicity and group-invariance. It is also demonstrated that the characterization in Pápai (2001) of sequential dictatorships for the case where assignments are not allowed to overlap is contained in the main result.
Keywords: D61; D63; D71; 330; Multiple assignments; overlapping assignments; sequential dictatorship; strategyproofness; compatibility